2020
DOI: 10.1038/s41598-020-73179-w
|View full text |Cite
|
Sign up to set email alerts
|

In silico analysis and in vivo assessment of a novel epitope-based vaccine candidate against uropathogenic Escherichia coli

Abstract: Uropathogenic Escherichia coli (UPEC) are common pathogens in urinary tract infections (UTIs), which show resistance to antibiotics. Therefore, there is a need for a vaccine to reduce susceptibility to the infection. In the present study, bioinformatics approaches were employed to predict the best B and T-cell epitopes of UPEC virulence proteins to develop a multiepitope vaccine candidate against UPEC. Then, the efficacy of the candidate was studied with and without Freund adjuvant. Using bioinformatics method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 53 publications
(64 reference statements)
1
25
0
Order By: Relevance
“…The approach of predicting and designing vaccines through in silico studies has improved massively in the last few years, where its applications extended to involve bacteria, viruses, fungi, and even cancer [26]. Multitope vaccine has been pre-dicted through computational approaches against several microorganisms such as Mayaro virus [27], Lassa virus [28], COVID-19 [29], and E. coli [30], where the predicted vaccine of the last study was expressed and analyzed through wet lab experimental validation and showed protection against urinary tract infection caused by uropathogenic E. coli in animal models. The application of immunoinformatics for designing NiV vaccine through epitope prediction was shown in many studies.…”
Section: Discussionmentioning
confidence: 99%
“…The approach of predicting and designing vaccines through in silico studies has improved massively in the last few years, where its applications extended to involve bacteria, viruses, fungi, and even cancer [26]. Multitope vaccine has been pre-dicted through computational approaches against several microorganisms such as Mayaro virus [27], Lassa virus [28], COVID-19 [29], and E. coli [30], where the predicted vaccine of the last study was expressed and analyzed through wet lab experimental validation and showed protection against urinary tract infection caused by uropathogenic E. coli in animal models. The application of immunoinformatics for designing NiV vaccine through epitope prediction was shown in many studies.…”
Section: Discussionmentioning
confidence: 99%
“…FyuA causes invasion of bacteria into the bloodstream from the urinary tract and is associated with highly pathogenic strains [ 19 , 42 ]. Various vaccines are being developed according to the mechanisms of virulence factors, mainly targeting adhesion molecules and iron metabolism [ 19 , 22 ]. Vaccines related to toxins have not yet achieved significant results [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Vaccines under development are targeting the virulence factors widely distributed in uropathogenic E. coli [ 16 , 18 21 ]. Most vaccines for uropathogenic E. coli primarily target adhesion molecules, iutA and fyuA [ 19 , 22 ]. E. coli can be categorized into four major groups, A, B1, B2, and D [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…The consensus sequences, without noise and formatting, were translated from nucleotides to amino acids, taking into account the percentage of identity for all isolates in a range of 97–100%. Hasanzadeh et al [ 35 ] confirm that the fimH sequence in UPEC strains maintains a 97% similarity percentage based on the results of the sequence homology of the fimH gene; thus, this urovirulent gene is associated with genetic variants and, therefore, could be clinically relevant. Nevertheless, it is known that the fimH gene is subjected to a strong selective pressure and it is likely to show a high degree of sequence heterogeneity contributing to a more precise characterization of the UPEC strains [ 36 ].…”
Section: Resultsmentioning
confidence: 99%